Circumferential distribution and location of Mallory-Weiss tears: recent trends - Okada, Mayumi; Ishimura, Norihisa; Shimura, Shino; Mikami, Hironobu; Okimoto, Eiko; Aimi, Masahito; Uno, Goichi; Oshima, Naoki; Yuki, Takafumi; Ishihara, Shunji; Kinoshita, Yoshikazu (Endoscopy International Open, 2015)
Background and study aims: Mallory-Weiss tears (MWTs) are not only a common cause of acute nonvariceal gastrointestinal bleeding but also an iatrogenic adverse event related to endoscopic procedures. However, changes in the clinical characteristics and endoscopic features of MWTs over the past decade have not been reported. The aim of this study was to investigate recent trends in the etiology and endoscopic features of MWTs.Patients and methods: We retrospectively reviewed the medical records of patients with a diagnosis of MWT at our university hospital between August 2003 and September 2013. The information regarding etiology, clinical parameters, endoscopic findings, therapeutic interventions, and outcome was reviewed.Results: A total of 190 patients with MWTs were evaluated. More than half (n = 100) of the cases occurred during endoscopic procedures; cases related to alcohol consumption were less frequent (n = 13). MWTs were most frequently located in the lesser curvature of the stomach and right lateral wall (2 – to 4-o’clock position) of the esophagus, irrespective of the cause. The condition of more than 90 % of the patients (n = 179) was improved by conservative or endoscopic treatment, whereas 11 patients (5.8 %) required blood transfusion. Risk factors for blood transfusion were a longer laceration (odds ratio [OR] 2.3) and a location extending from the esophagus to the stomach (OR 5.3).Conclusions: MWTs were frequently found on the right lateral wall (2 – to 4-o’clock position) of the esophagus aligned with the lesser curvature of the stomach, irrespective of etiology. Longer lacerations extending from the esophagus to the gastric cardia were associated with an elevated risk for bleeding and requirement for blood transfusion.